The Effect of Low-Modulus Plastic Fiber on the Physical and Technical Characteristics of Modified Heavy Concretes Based on Polycarboxylates and Microsilica - Akhmetov, D.A.; Pukharenko, Y.V.; Vatin, N.I.; Akhazhanov, S.B.; Akhmetov, A.R.; Jetpisbayeva, A.Zh.; Utepov, Y.B. (Materials, 2022)
Manufacturers of building materials strive to optimize the three basic concrete properties— strength, durability, and shrinkage deformation, of which the focus is generally on the durability in the structure when designing and monitoring the poured concrete. Studying concretes’ structural performance and the change in their characteristics over time enables the solution of many important issues associated with the design of reliable, durable, and cost-effective buildings and structures. This article presents studies aimed at improving the physical, technical, and operational characteristics of cement concrete and reducing cement consumption in heavy concretes through the use of complex modifiers and volumetric fiber reinforcement. Four concrete compositions of widely recognized grades were developed, of which samples were molded and tested for compressive and flexural strength, frost resistance, volumetric water absorption, and density. Test results confirmed the possibility of binder (cement) economy up to 18% and increasing frost resistance up to W300 when using microsilica, reduction in volumetric water absorption of up to 40% when using both microsilica and hyperplasticizer, and increasing flexural strength by over 30% when using polymer fiber. The developed compositions passed the industrial tests, and were successfully introduced in the production process of the operating reinforced concrete products’ manufacturer
Keywords: durability; modifiers; hyperplasticizers; fibers; heavy concrete; microsilica